2014
DOI: 10.1016/j.jevs.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intraocular Leptospira Infections in the Pathogenesis of Equine Recurrent Uveitis in the Southern United States

Abstract: The results of our study identified a population of ERU cases with an active intraocular Leptospira infectious process in the Southern United States. The diagnosis of intraocular leptospirosis required ocular fluid sampling for PCR or culture. Twenty-one percent of ocular fluid samples were positive by culture and forty-five percent by PCR; no control horses were positive by either culture or PCR. These findings are in contrast to a recent study from the Southeastern US that showed no evidence of bacterial DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 25 publications
2
59
1
1
Order By: Relevance
“…and ERU (Brandes et al 2007, Bryans 1955, Davidson et al 1987, Polle et al 2014, von Borstel et al 2010, Wollanke et al 2000, Wollanke et al 2001. In these studies, the amount of positive results for intraocular leptospiral antibodies ranged between 35 and 94 % (Brandes et al 2007, Dorrego-Keiter 2016, Gerding et al 2015, Gilger et al 2008, Polle et al 2014, von Borstel et al 2010, Wollanke et al 2001) of the eyes tested. In the present study the positive MAT-results ranged between 41 and 51% in L1 and L3.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…and ERU (Brandes et al 2007, Bryans 1955, Davidson et al 1987, Polle et al 2014, von Borstel et al 2010, Wollanke et al 2000, Wollanke et al 2001. In these studies, the amount of positive results for intraocular leptospiral antibodies ranged between 35 and 94 % (Brandes et al 2007, Dorrego-Keiter 2016, Gerding et al 2015, Gilger et al 2008, Polle et al 2014, von Borstel et al 2010, Wollanke et al 2001) of the eyes tested. In the present study the positive MAT-results ranged between 41 and 51% in L1 and L3.…”
Section: Discussionmentioning
confidence: 93%
“…But it was shown that these intraocular leptospiral traces can be detected in aqueous humor, too (Faber et al 2000, Polle et al 2014, Schwink et al 1989, Tömördy et al 2010. A steady-state passive diffusion between the vitreous body and the aqueous humor has been described in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other possible diagnostic tests to determine the cause of uveitis include evaluating aqueous humour leptospiral titres, aqueous humour leptospiral PCR and aqueous humour culture (Gerding and Gilger ; Polle et al . ). It was not performed due to concerns for complications such as causing more inflammation (Featherstone and Heinrich ).…”
Section: Discussionmentioning
confidence: 97%